Comparison of Once-Daily Subcutaneous Fragmin® with Continuous Intravenous Unfractionated Heparin in the Treatment of Deep Vein Thrombosis - Lindmarker, Per; Holmström, Margareta; Granqvist, Staffan; Johnsson, Hans; Lockner, Dieter (Thrombosis and Haemostasis, 1994)
Two hundred and four consecutive patients with venographically confirmed deep vein thrombosis (DVT) were randomised either to a low molecular weight heparin, Fragmin®, administered subcutaneously (s.c.) once daily as a fixed dose of 200IU anti-factor Xa/kg or to continuous intravenous infusion of unfractionated heparin (UFH). The UFH dose was adjusted to maintain the activated partial thromboplastin time between 1.5 and 3.0 times the upper limit of the reference value at each centre. Fragmin® or UFH was given for a minimum of 5 days until anticoagulation with warfarin, given from day 1, was established (i. e. an International Normalised Ratio, of 2.0−3.0). A second venogram was obtained after Fragmin® or UFH treatment. There were no significant differences in the change in mean Marder score before and after treatment between the two treatment groups, irrespective of thrombus localisation. No major bleeding events, symptomatic pulmonary embolism, symptomatic thrombosis progression or death occurred during hospitalisation. Eight documented venous thromboembolic events occurred before the follow-up visit 6 months after randomisation: 5 in patients treated with Fragmin® and 3 in those treated with UFH. Six of these events occurred after cessation of warfarin treatment. In conclusion Fragmin® given s.c. once daily in a fixed dose adjusted for body weight, is no less effective or safe than a continuous infusion of UFH in the initial treatment of acute DVT.